Fatores associados à aquisição nosocomial de bacilos gram-negativos no Hospital das Clínicas da Faculdade de Medicina de Botucatu em diferentes estações do ano: um estudo tipo caso-controle - Rodrigues, Fernanda Saad [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
Seasonality of healthcare-associated infections (HCAIs) has been recently reported, especially involving Gram-negative bacilli (GNB). Factors underlying this phenomenon were not elucidated. It is theoretically conceivable it reflects seasonal variations in traditional risk factors for those infections. With this in mind, we conducted a study to analyze the interplay of season, weather and usual predictors of healthcare-associated bloodstream infections caused by Gram-negative bacilli (GNB-BSI). The study had a retrospective, case-only desing. It was conducted in the teaching hospital from Botucatu School of Medicine (450 beds). The study enrolled 446 patients with GNB-BSI caused by Escherichia coli, Enterobacter spp., Klebsiella spp., Pseudomonas aeruginosa or Acinetobacter baumannii, diagnosed from July 2012 through June 2016. Demographic data, comorbidities, invasive procedures and use of antimicrobials were reviewed in medical charts. The season in which GNB-BSI occurred, as well as weather parameters of the day of diagnosis, were recorded. We analyzed factors associated with occurrence of GNB-BSI in different seasons (with winter as reference category) and caused by different GNB (reference category, E. coli). Univariate and multivariable models of polytomous (multinomial) logistic regressions were used for analysis. In multivariable analysis, GNB-BSI diagnosed in summer were more likely to be caused by Klebsiella spp. (OR, 5.33; 95%CI, 2.04-13.96) or A. baumannii (OR, 2.69; 95%CI, 1.04-6.96), and there was association of Klesbiella spp. and spring (OR, 2.86; 95%CI, 1.14-7.18). Average temperature (in Celsius degrees[°C]) in the day of diagnosis was associated with Klebsiella spp. (OR, 1.19; 95%CI, 1.07-1.33) and A. baumannii (OR, 1.20; 95%CI, 1.07-1.34). In conclusion, warm seasons and daily temperature impact on the etiology of GNB-BSI, even in models adjusted for usual risk factors. Our findings support the thesis that seasonality of healthcare-associated pathogens is intrinsic to microorganisms, and not associated with comorbidities, procedures or use of antimicrobials.

Seasonality of healthcare-associated infections (HCAIs) has been recently reported, especially involving Gram-negative bacilli (GNB). Factors underlying this phenomenon were not elucidated. It is theoretically conceivable it reflects seasonal variations in traditional risk factors for those infections. With this in mind, we conducted a study to analyze the interplay of season, weather and usual predictors of healthcare-associated bloodstream infections caused by Gram-negative bacilli (GNB-BSI). The study had a retrospective, case-only desing. It was conducted in the teaching hospital from Botucatu School of Medicine (450 beds). The study enrolled 446 patients with GNB-BSI caused by Escherichia coli, Enterobacter spp., Klebsiella spp., Pseudomonas aeruginosa or Acinetobacter baumannii, diagnosed from July 2012 through June 2016. Demographic data, comorbidities, invasive procedures and use of antimicrobials were reviewed in medical charts. The season in which GNB-BSI occurred, as well as weather parameters of the day of diagnosis, were recorded. We analyzed factors associated with occurrence of GNB-BSI in different seasons (with winter as reference category) and caused by different GNB (reference category, E. coli). Univariate and multivariable models of polytomous (multinomial) logistic regressions were used for analysis. In multivariable analysis, GNB-BSI diagnosed in summer were more likely to be caused by Klebsiella spp. (OR, 5.33; 95%CI, 2.04-13.96) or A. baumannii (OR, 2.69; 95%CI, 1.04-6.96), and there 16 was association of Klesbiella spp. and spring (OR, 2.86; 95%CI, 1.14-7.18). Average temperature (in Celsius degrees[°C]) in the day of diagnosis was associated with Klebsiella spp. (OR, 1.19; 95%CI, 1.07-1.33) and A. baumannii (OR, 1.20; 95%CI, 1.07-1.34). In conclusion, warm seasons and daily temperature impact on the etiology of GNB-BSI, even in models adjusted for usual risk factors. Our findings support the thesis that seasonality of healthcareassociated pathogens is intrinsic to microorganisms, and not associated with comorbidities, procedures or use of antimicrobials.
Seasons, weather and predictors of healthcare-associated Gram-negative bloodstream infections: a case-only study
Keywords: infecções relacionadas à assistência à saúde; bacilos gram-negativos; infecções da corrente sanguínea; sazonalidade; meteorologia; healthcare-associated infections; gram-negative bacilli; bloodstream infections; seasonality; meteorology